Hydranencephaly in a Child with Congenital Cytomegalovirus Infection- A Clinicoradiological Perspective - Lokesh Meena; Miranda Devi Keisham; Pooja Kundu; Rahul Dev (International Journal of Anatomy Radiology and Surgery, 2022)
Hydranencephaly (HE) is a rare congenital anomaly in which there is a complete or near complete absence of bilateral cerebral hemispheres which are replaced by a membranous sac filled with Cerebrospinal Fluid (CSF). Thalami, brainstem, and cerebellar hemisphere are preserved. A small island of cerebral parenchyma may also be seen along the inner aspect of the calvarium. Several theories regarding its aetiopathogenesis have been postulated with the hypothesis of bilateral occlusion of supraclinoid segment of Internal Carotid Artery (ICA) being widely accepted. The authors present a case of a two-month-old male child presenting with increasing head size since birth, associated hydrocephalus and residual parenchymal sleeve visualised on neurosonogram and calcifications depicted on computed tomography. The diagnosis of Cytomegalovirus (CMV) was confirmed serologically and further neurosurgical consultation was advised for increasing head size secondary to hydrocephalus. The HE is usually detected in the second trimester, however can also occur in early or later gestation and has a very poor prognosis.